Dihydroxylation Studies of Isoquinolinones: Synthesis of the EF-Ring of Lysolipin I - Heinemann, Maximilian J. B.; Voigt, Thomas; Menche, Dirk (Synthesis, 2021)
Inspired by the potent polycyclic xanthone antibiotic lysolipin I, a general study on asymmetric dihydroxylation reactions of variously substituted isoquinolinones was performed. Different isoquinolinones were efficiently prepared, either by a Pomeranz–Fritsch type condensation or a Curtius rearrangement. Under a broad variety of conventional oxygenation procedures, they proved very unreactive. However, either by suitable substitution of the appending aromatic ring or more forcing conditions a dihydroxylation could finally be performed, which allowed the synthesis of the EF-ring of lysolipin I.
Keywords: lysolipin I; Pomeranz–Fritsch cyclization; Curtius rearrangement; asymmetric dihydroxylation; isoquinolinone